2018
DOI: 10.3390/su10082659
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Influence of Real Estate Development on Private Investment: A Case Study of China

Abstract: Private investment in China, as a developing country, is an important source of financing for Chinese SMEs (Small and Medium-Size Enterprises) and has played a major role in the development of the real economy. However, in 2016, the growth rate of private investment in China dropped from 10.18% to 3.17%, which had a significant impact on the real economy. At the same time, China’s real estate market has developed rapidly, attracting a large number of capital inflows. The relationship between real estate develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…In this research, the economic development level indicator has the highest weight value in the evaluation indicator system, which means that the economic development level is an important indicator in the urbanization process. Li et al and Liu et al , respectively, focus on the impact of individual investment and population flow on housing prices in the urbanization process, demonstrating the close relationship between urbanization and housing prices [73,74]. In this study, the urbanization process and housing prices show high coupling in the system, which indicates that there is a close coupling coordination relationship between them.…”
Section: Discussionmentioning
confidence: 54%
“…In this research, the economic development level indicator has the highest weight value in the evaluation indicator system, which means that the economic development level is an important indicator in the urbanization process. Li et al and Liu et al , respectively, focus on the impact of individual investment and population flow on housing prices in the urbanization process, demonstrating the close relationship between urbanization and housing prices [73,74]. In this study, the urbanization process and housing prices show high coupling in the system, which indicates that there is a close coupling coordination relationship between them.…”
Section: Discussionmentioning
confidence: 54%
“…[7] examines the influencing factors to economic in Sichuan province in China using Basso, and find that real estate growth rate on economic growth in Sichuan is not significant. [8] examines whether real estates market affects the private investments, and find that the growth of the real estates market has an important impact on the private investment's growth. [9] examines how real estates fluctuations affects China's economic fluctuations using OLS and Granger causality test, and find that real estate industry is the most powerful pull of China's economic growth momentum.…”
Section: Revised Manuscript Received On July 22 2019mentioning
confidence: 99%
“…Gerdesmeier et al (2010) found that investment has a profound impact on the development of the real estate industry, and the scale of investment changes can be used to predict the rise and fall of real estate [ 18 , 19 ]. Therefore, this article uses real estate investment to measure the degree of real estate development.…”
Section: Introductionmentioning
confidence: 99%